The impact of training on productivity and wages: firm level evidence - Jozef Konings; Stijn Vanormelingen (Institute for the Study of Labor (IZA), 2010)
This paper uses firm level panel data of firm provided training to estimate its impact on productivity and wages. To this end the strategy proposed by Ackerberg, Caves and Frazer (2006) for estimating production functions to control for the endogeneity of input factors and training is applied. The productivity premium for a trained worker is estimated at 23%, while the wage premium of training is estimated at 12%. Our results give support to recent theories that explain work related training by imperfect competition in the labor market.
Keywords: J24; J31; L22; 330; Training; production functions; human capital; Berufsbegleitende Ausbildung; Arbeitsproduktivität; Lohnniveau; Arbeitsmarkt; Monopson; Lohnverhandlungen; Belgien